2011
DOI: 10.1126/science.1202997
|View full text |Cite
|
Sign up to set email alerts
|

Residue-Specific Vibrational Echoes Yield 3D Structures of a Transmembrane Helix Dimer

Abstract: Two dimensional vibrational echo spectroscopy has previously been applied to structural determination of small peptides. Here we extend the technique to a more complex, biologically significant system: the homodimeric transmembrane dimer from the α-chain of the integrin αIIbβ3. We prepared micelle suspensions of the pair of 30-residue chains that span the membrane in the native structure, with varying levels of heavy (13C=18O) isotopes substituted in the backbone of the central 10th through 20th positions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
128
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 36 publications
1
128
0
Order By: Relevance
“…[1][2][3] Delocalized amide I states provide sensitivity to secondary structure, while local peptide conformations can be probed by studying individual sites along the protein backbone, usually via isotope labels. [4][5][6][7] Although the rich information content of amide I spectra has been appreciated for many years, the complexity and congestion of the absorption spectra and the difficulty of accurately predicting the spectral features of individual protein structures have in many ways limited the utility of amide I spectroscopy in answering detailed structural questions. More recently, the advent of two-dimensional infrared (2DIR) spectroscopy has begun to assist in overcoming amide I spectral congestion, [8][9][10] while on the theoretical front, spectroscopic "maps" linking protein structure to specific spectral features have greatly improved our ability to interpret experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Delocalized amide I states provide sensitivity to secondary structure, while local peptide conformations can be probed by studying individual sites along the protein backbone, usually via isotope labels. [4][5][6][7] Although the rich information content of amide I spectra has been appreciated for many years, the complexity and congestion of the absorption spectra and the difficulty of accurately predicting the spectral features of individual protein structures have in many ways limited the utility of amide I spectroscopy in answering detailed structural questions. More recently, the advent of two-dimensional infrared (2DIR) spectroscopy has begun to assist in overcoming amide I spectral congestion, [8][9][10] while on the theoretical front, spectroscopic "maps" linking protein structure to specific spectral features have greatly improved our ability to interpret experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 According to the current paradigm, water works as a building block and a lubricant for the biomachinary of the cell, and as an energy and charge transfer agent. 6 During the last few decades, various studies indicated that a broad distribution of water sites exists inside the proteins 7 and lipid layers making water a constitutive part of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Because the stability of the monomeric α-helix depends strongly on the number of consecutively repeating helical turns (12, 33), we chose an initial structure consisting of a preformed helix and introduced a small distortion associated mainly with one helical turn in the central region. After photochemical release of the S,S-tetrazine constraint, the structural reorganization (34,35) is examined by means of the transient 2D IR of 13 …”
Section: Significancementioning
confidence: 99%